Case report: Ten cases of acquired idiopathic generalized anhidrosis treated with oral pilocarpine - Hanako Miyahara; Noriko Kubota; Mari Okune; Yoshiyuki Ishii; Naoko Okiyama; Toshifumi Nomura; Junichi Furuta (Frontiers Media S.A., 2024)
Acquired idiopathic generalized anhidrosis is a rare disease characterized by systemic anhidrosis or hypohidrosis without other systemic diseases. However, its etiology remains unclear. Autoimmune mechanisms seem to be involved in the development of acquired idiopathic generalized anhidrosis. Although steroid pulse therapy is the most commonly used therapy, it lacks a high level of evidence. On the other hand, pilocarpine, a muscarinic receptor agonist that stimulates exocrine glands, increases saliva and tear secretion as well as sweating. Here, we report treatment progresses of steroid pulse therapy and oral pilocarpine in our department. Between 2012 and 2021, we treated 10 patients of acquired idiopathic generalized anhidrosis. All patients were administered oral pilocarpine as the first therapy, three (30%) of whom had increased sweating. Minor side effects were observed, however, no serious side effects were observed. Five patients who did not respond to oral pilocarpine were subsequently treated with steroid pulse therapy to which four (80%) showed significant response. Two patients were subsequently administered oral pilocarpine as post-therapy, and remission was maintained for up to 81 months. Oral pilocarpine could be used to relieve symptoms in patients with acquired idiopathic generalized anhidrosis prior to steroid pulse therapy and as maintenance therapy after steroid pulse therapy.